Analisis Diftong pada Video Ceramah Sayyid Muhammad Al-Alawi menit ke-6 hingga ke-10: Eksplorasi fonologi - Hidayah, Shilfina (Maliki Interdisciplinary Journal, 2026)
In the Arabic language, there are only two diphthong sounds, namely /au/ and /ai/, both of which are classified as rising diphthongs because the first sound is positioned lower than the second sound. This study aims to analyze sentences containing diphthongs in excerpts from a lecture by a prominent scholar. A diphthong is defined as a combination of two vowel sounds pronounced in one breath, and can be distinguished into rising diphthongs and falling diphthongs. The research method used in this study is descriptive qualitative with an ashwat science approach, focusing on the study of diphthongs so that sentences containing diphthongs can be analyzed. The analysis results show that in the YouTube lecture by Sayyid Muhammad, which narrates the story and poetry of the birth of the Prophet Muhammad, there are eighteen sentences containing diphthongs. This research is expected to serve as a useful reference for linguists, language teachers, and students who wish to study the complex aspects of language, and as a development of language rules.